Tax efficient supply chain management - Luo, Jing (2015)
This project focuses on the emerging trend of global outsourcing and Tax-Efficient Supply Chain Management (TESCM). With literature review from both logistics and tax journals, the project identifies the performance measures of each side and evaluates the conflicts between them. The project subsequently exemplifies the level of alignment between tax and logistics considerations under the hub-spoke structure by the case study of the distribution network of SDV Logistics Company. Through balancing different measures in both logistics and tax domains, the hub-spoke structure is justified with the potential of TESCM and the following challenges are highlighted as additional variables which influence decision making for TESCM.